A New Mode of Visible Fracture System in Coal Seams and Its Implications for Coalbed Methane Seepage. (11th April 2023) - Li, Rui; Jin, Lihong; Wang, Shengwei; Liu, Heping; Cui, Zhigang; Xiang, Wenting
Abstract : As the central flow channel for fluid seepage through rock layers, the visible fracture system (VFS) significantly affects geoenergy extraction for petroleum, natural gas, geothermal resources, and greenhouse gas sequestration. In this work, we propose a new mode of VFS in coal seams, including hydraulic fractures, exogenetic fractures, interlayer fractures, gas-expanding fractures, and cleats. The development characteristics of VFSs in coal seams are analyzed, including containing their geometry, orientation, scale, distribution, and connection between each other. Furthermore, the implications of the VFS for fluid (gas and water) and solid (coal fines) flow through coal seams are discussed. The development of the VFS determines the effective flow conductivity, affecting the flow of gas, water, and coal fines. Additionally, as the reservoir pressure transfer channel, the VFS significantly influences depressurization with reservoir depletion, determining the extension of the methane desorption range. The exogenetic fractures and interlayer fractures dominate the expansion of the primary hydraulic fractures, and gas-expanding and cleats usually control the branch of hydraulic fractures. Furthermore, we find that the daily production rate distribution of most CBM wells presents a particular banded, L-shaped, or T-shaped pattern. It is thought that the VFS dominates the productivity of CBM in coal seams. The field production data also provide evidence that the occurrence of the VFS makes the CBM reservoir heterogeneous. This study presents a recommended framework involving the characteristics of the VFS and its influences on CBM production.